Data anggaran dan kegiatan Iptek, Departemen, dan Non Departemen (Pusat Analisa Perkembangan Ilmu Pengetahuan dan Teknologi, Lembaga Ilmu Pengetahuan Indonesia, 1994)
Budget and activities of research and development for science and technology in governments and non-government depatments in Indonesia.